Tonally Teen? Issues of Audience Appeal in Contemporary Danish Youth Films - Lysne, Anders (Academic Quarter | Akademisk kvarter, 2013)
This article investigates the trial and error of audience appeal in contemporary Danish youth films supported through the special children’s and youth film commissioner scheme of The Danish Film Institute. Employing the concept of tone to textual analysis, the article focuses on the two films Triple Dare (Christina Rosendahl, 2006) and Skyscraper (Rune Schjøtt, 2011), which serve as an interesting comparison for being, respectively, the most and the least commercially successful of the publicly funded youth films in the 2000s. With the analysis of these films, I aim to explicate how tonal complexity may affect audience involvement and complicate the fundamental issue of audience appeal.